The secret garden - Burnett, Frances Hodgson, 1849-1924. (New York : New American Library, 2003)
A ten-year-old orphan comes to live in a lonely house on the Yorkshire moors where she discovers an invalid cousin and the mysteries of a locked garden.
ARC
Keywords: Orphans -- Fiction; Gardens -- Fiction; People with disabilities -- Fiction; Yorkshire (England) -- History -- 20th century -- Fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Fiction; Yorkshire (England) -- Fiction